Argentina Since the 2001 Crisis : Recovering the Past, Reclaiming the Future - Levey, Cara.; Ozarow, Daniel; Wylde, Christopher; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This timely and interdisciplinary volume analyzes the many impacts of and contrasting responses to the Argentine political, economic, and social crises of 2001-02. Chapters offer original theoretical models and examine the relationship between political, cultural, economic, and societal spheres.
Keywords: Political science; Ethnology -- Latin America; Political economy; Latin America -- Politics and government; Economic policy; Cultural studies; Political Science and International Relations; Latin American Politics; Economic Policy; Latin American Culture; Political Science; Cultural Studies; Political Economy